PARALLEL PRECEDENCE CONSOLIDATION FOR SIMILAR WORKLOAD IN CLOUD - Srinivas, A.; J, Stalin Babu; Kumar, A Praveen; Gupta, K Gurunadha (IJRDO -Journal of Computer Science Engineering, 2015)
Cloud computing allows business customers to scale up and down their resource usage based onneeds. Many of the routed gains in the cloud model come from resource multiplexing throughvirtualization technology. In this paper, we present a system that uses virtualization technology toallocate data center resources dynamically based on application demands and support greencomputing by optimizing the number of servers in use. We introduce the concept of “skewness”to measure the unevenness in the multi-dimensional resource utilization of a server. By minimizingskewness, we can combine different types of workloads nicely and improve the overall utilizationof server resources. We develop a set of Green Computing techniques that prevent overload in thesystem effectively while saving energy used. Trace driven simulation and experiment resultsdemonstrate that our algorithm achieves good performance by Resource Management.